The Romani diaspora - Toyansk, Marcos (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
As a scattered population without a homeland, the case of the Romanies is interesting and very relevant for the study of how a dispersed and diasporic group may try to achieve autonomy without establishing a state with its own territory. At the same time, it invites us to consider in what ways the scattered and very diverse Romani groups can create a transnational community, since they have shown very different features and needs. This paper focuses mainly on Brazil, where many Romanies from different backgrounds live, in order to analyze the Romani Evangelism development of intra-state and transstate networks among co-ethnics, describing its spatial approaches and territories and comparing it to the notion of dispersion condition as a de-territorialized one. As a process capable of connecting Romani communities worldwide, Romani Evangelism can become an umbrella under which the various groups are brought together, enabling the rise of a transnational community.
Keywords: transnacionalizem; Romi; diaspora; binkošništvo; evangelizem